Current status of brachytherapy in cancer treatment – short overview - Skowronek, Janusz (Journal of Contemporary Brachytherapy, 2017)
Cancer incidence and mortality depend on a number of factors, including age, socio-economic status and geographical location, and its prevalence is growing around the world. Most of cancer treatments include external beam radiotherapy or brachytherapy. Brachytherapy, a type of radiotherapy with energy from radionuclides inserted directly into the tumor, is increasingly used in cancer treatment. For cervical and skin cancers, it has become a standard therapy for more than 100 years as well as an important part of the treatment guidelines for other malignancies, including head and neck, skin, breast, and prostate cancers. Compared to external beam radiotherapy, brachytherapy has the potential to deliver an ablative radiation dose over a short period of time directly to the altered tissue area with the advantage of a rapid fall-off in dose, and consequently, sparing of adjacent organs. As a result, the patient is able to complete the treatment earlier, and the risks of occurrence of another cancer are lower than in conventional radiotherapy treatment. Brachytherapy has increased its use as a radical or palliative treatment, and become more advanced with the spread of pulsed-dose-rate and high-dose-rate afterloading machines; the use of new 3D/4D planning systems has additionally improved the quality of the treatment. The aim of the present study was to present short summaries of current studies on brachytherapy for the most frequently diagnosed tumors. Data presented in this manuscript should help especially young physicians or physicists to explore and introduce brachytherapy in cancer treatments.